Supporting Pregnant Aboriginal and Torres Strait Islander Women to Quit Smoking: Views of Antenatal Care Providers and Pregnant Indigenous Women - Passey, Megan E. (Matern Child Health J, 2013)
To assess support for 12 potential smoking cessation strategies among pregnant Australian Indigenous women and their antenatal care providers. Cross-sectional surveys of staff and women in antenatal services providing care for Indigenous women in the Northern Territory and New South Wales, Australia. Respondents were asked to indicate the extent to which each of a list of possible strategies would be helpful in supporting pregnant Indigenous women to quit smoking. Current smokers (n = 121) were less positive about the potential effectiveness of most of the 12 strategies than the providers (n = 127). For example, family support was considered helpful by 64 % of smokers and 91 % of providers; between 56 and 62 % of smokers considered advice and support from midwives, doctors or Aboriginal Health Workers likely to be helpful, compared to 85–90 % of providers. Rewards for quitting were considered helpful by 63 % of smokers and 56 % of providers, with smokers rating them more highly and providers rating them lower, than most other strategies. Quitline was least popular for both. This study is the first to explore views of pregnant Australian Indigenous women and their antenatal care providers on strategies to support smoking cessation. It has identified strategies which are acceptable to both providers and Indigenous women, and therefore have potential for implementation in routine care. Further research to explore their feasibility in real world settings, uptake by pregnant women and actual impact on smoking outcomes is urgently needed given the high prevalence of smoking among pregnant Indigenous women.